A Review Study on Effectiveness of Co-operative Learning Teaching Learning Process (International Journal of Food and Nutritional Sciences, 2022)
The struggle to resolve potential conflicts during collaborative activity results in the development of higher levels of understanding (Bukunola& Idowu, 2012). The elaboration theory suggests that one of the most effective means of learning is to explain the material to someone else. Cooperative learning activities enhance elaborative thinking and more frequent giving and receiving of explanations, which has the potential to increase the depth of understanding, the quality of reasoning, and the accuracy of long term retention .The implementation of cooperative learning method many methods are used. These methods display diversity depending on the number of students, the social structure of the environment, the physical structure of the class and applied to the subject of the course and course (Maloof & White, 2005; Şimşek et al., 2008). Cooperative learning method has taken place of education activities for a long time. During this process, researchers have developed various methods and practices (McTighe & Lyman, 1988; Jones & Steinbrink, 1991; Almasi, 1995; Gambrell, 1996). The forefronts of these methods are Learning Together, Student Teams, Group Investigation, Let's Ask and Learn Together, Jigsaw, and the Reading-Writing-Presentation method. od.).